My Tibetan Childhood : When Ice Shattered Stone - Nus-blo, Nags-tshang, 1949- (Book collections on Project MUSE., 2014)
A bestseller in Tibet until it was banned by China, this moving memoir chronicles Naktsang Nulo's childhood in Tibet's Amdo region during the uprising against the Chinese invasion of the 1950s.